SISTEM KEARSIPAN UNTUK MENUNJANG EFISIENSI KERJA DI BAGIAN TATA USAHA DIREKTORAT I PADA INSPEKTORAT JENDERAL KEMENDIKBUDRISTEK RI - Ayudia, Rosalina; Haryanto, Haryanto; Lailani, Evi Okli (ITB Swadharma, 2022)
This study discusses the Application of the Archives System to Support Work Efficiency in the Administration Section of the Inspectorate I of the Inspectorate General of the Ministry of Education, Culture, Research, and Technology. The purpose of this research is to find out how to implement the filing system to support work efficiency and what obstacles are encountered. The results showed that the application of the filing system in supporting work efficiency in the Administrative Section of the Inspectorate I at the Inspectorate General of the Ministry of Education, Culture, Research, and Technology includes storage, organization, borrowing, retrieval, maintenance, and destruction. The application of this archive has been running quite well according to existing regulations. However, there are still some things that have not supported work efficiency that must be improved to facilitate the implementation of archives.Penelitian ini membahas mengenai Penerapan Sistem Kearsipan dalam Menunjang Efisiensi Kerja di Bagian Tata Usaha Inspektorat I pada Inspektorat Jenderal Kementerian Pendidikan, Kebudayaan, Riset dan Teknologi. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana penerapan sistem kearsipan untuk menunjang efisiensi kerja dan kendala-kendala apa saja yang dihadapi. Hasil penelitian menunjukan bahwa penerapan sistem kearsipan dalam menunjang efisiensi kerja di Bagian Tata Usaha Inspektorat I pada Inspektorat Jenderal Kementerian Pendidikan, Kebudayaan, Riset dan Teknologi meliputi penyimpanan, pengorganisasian, peminjaman, penemuan kembali, pemeliharaan dan pemusnahan. Penerapan kearsipan ini sudah berjalan cukup baik sesuai ketentuan yang ada. Namun, masih ada beberapa hal yang belum menunjang efisiensi kerja yang harus diperbaiki agar mempermudah pelaksanaan kearsipan.